2011
DOI: 10.1002/clen.201000497
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic Restoration of Sulfate‐Accumulated Saline Greenhouse Soil

Abstract: Electrokinetic (EK) process was performed to restore sulfate-originated saline soil and to evaluate the effect of treatment duration. Sulfate and potassium were the major ionic salts in the saline soil used in this study. A constant voltage gradient of 1 V/cm was applied for 8, 12, and 16 days. After EK treatment, anions and cations were transported toward anode and cathode, respectively, by electromigration. Chloride was completely removed, and 85.6% of nitrate was removed after 8 days of treatment. The incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…Electromigration, namely the transportation of ions toward oppositely charged electrodes, is the major mechanism for separating and removing salts ). Electrokinetic process was performed by Cho et al (2011) to restore sulfate-originated saline soil and to evaluate the effect of treatment duration, and found that after electrokinetic treatment, the electrical conductivity (EC) of the soil, an indicator of soil salinity, decreased to 1.93 dS×m 1 from an initial value of 5.3 dS×m 1 and the distribution of sulfate was similar to that of EC. By using column techniques the present study has been conducted to assess efficiency of electrochemical process to reclaim saline-sodic soils using.…”
Section: Introductionmentioning
confidence: 99%
“…Electromigration, namely the transportation of ions toward oppositely charged electrodes, is the major mechanism for separating and removing salts ). Electrokinetic process was performed by Cho et al (2011) to restore sulfate-originated saline soil and to evaluate the effect of treatment duration, and found that after electrokinetic treatment, the electrical conductivity (EC) of the soil, an indicator of soil salinity, decreased to 1.93 dS×m 1 from an initial value of 5.3 dS×m 1 and the distribution of sulfate was similar to that of EC. By using column techniques the present study has been conducted to assess efficiency of electrochemical process to reclaim saline-sodic soils using.…”
Section: Introductionmentioning
confidence: 99%
“…전기동력학적 정화기술은 이온성 오염물질을 토양 으로부터 제거하기 위해 고안된 방법이다 (박성우 외, 2008; 조정민 외, 2009; 박근용 외, 2010). 최근의 연구 결과에 의하면 전기동력학적 방법은 염류집적 토양에서 염류를 효과적으로 제거할 수 있다고 보고되었다 (Jia et al, 2005;Cho et al, 2009Cho et al, , 2010Cho et al, , 2011Ha et al, 2009;Kim et al, 2011;Lee et al, 2011). Cho et al(2009 (정병간 외, 1998).…”
Section: 염류집적 농경지의 경우 직접적인 정화기술을 적용하기unclassified
“…Bioremediation and chemical restoration are less effective, time-consuming and extremely expensive [10,11]. Recently, the Electrokinetic (EK) technique has removed salts from saline soil in a laboratory scale [12][13][14] and pilot-scale works [15][16][17]. Many studies on desalination using EK remediation have been reported [18][19][20].…”
Section: Introductionmentioning
confidence: 99%